P56 Bleedin' heck!. (5th November 2017) - Ferguson, KJ; Jakeman, N
Abstract : Background: Major Haemorrhage Protocols (MHP) vary from hospital to hospital and trainees, who are often the ones activating it, rotate hospitals every few months to a year. The 'unknown-unknowns' that result from this situation can lead to a critical incident. For example, in some hospitals you will receive blood, a dedicated porter and a medical emergency team, whereas in others only the lab is alerted to get the blood ready but no team is dispatched. Over 50% of senior staff in our Emergency Department (ED) were not aware that you do not get a porter with the MHP Aim: To system test the MHP in our District General Hospital. Methodology: We ran an in-situ simulation in real time in our ED. The simulation was as follows: A 35 year old man was found collapsed by his girlfriend in his flat. There was evidence of hematemesis and melaena throughout the flat. He had a background of alcohol excess and previous varices. The simulated patient was booked into our systems and therefore had a hospital number and other identifiers. Switchboard and the lab were informed that the simulation would be happening, we created simulated blood products with corresponding patient identifiers and it was run in real time with the staffing levels that were available. We used a low fidelity manikin, SIMMON technology and walkie-talkies for patient voice. The simulation was followed by a debrief, together with the transfusion staff. The results of this were presented and discussed at the ED Clinical Governance meeting and Hospital Transfusion meeting. Outcomes: By increasing the fidelity of this SIM we were able to accurately test the system response to a major haemorrhage and identify areas for improvement. Learning Points: 1) there is no porter with the MHP 2) doctors do not have a barcode to access blood 3) location of the lab 4) remember to stand down the MHP. As a result of this system test all staff have been made aware of the nuances of the MHP in this hospital, the Emergency Department Assistants have been added to the MHP bleep and the phone in resus has been changed to a portable one. Recommendations: All MHPs should be system tested and all staff should be aware of the nuances of their protocol.